CP-188 Evaluation of patient's knowledge about vitamin k antagonist treatment. (25th February 2017) - Berdi, F; Tadlaoui, Y; Fahry, A; Zbir, M; Bennana, A; Bousliman, Y
Abstract : Background: Vitamin K antagonist (VKA) is thought to be the largest anticoagulant prescribed; its iatrogenic effect constitutes a real public health problem. Purpose: The objective of this study was to evaluate the level of knowledge of patients about VKA treatment. Material and methods: During September and October, a standardised questionnaire was submitted to external patients consulting in the department of cardiology and receiving VKA. Criteria for inclusion were as follows: patients >18 years, receiving VKA and who agreed to participate in the study. The items on the questionnaire allowed identification of the main areas of therapeutic education: knowledge (knowledge of treatment by the patient, treatment modalities), know-being (healthy living, communication with health professionals) and know-how (management processing). All patients gave their informed consent. Data analysis was performed using the SPSS 13.0 software. Results: 30 patients were included in the study, 48% men and 51% women. Mean age was 55 years and 31% were illiterate. The name of the VKA treatment was known in 96% and 100% of patients who knew their dosage. 68% knew the indication for VKA treatment. 89% declared having received information about their treatment, 65% by their doctor and 34% by their pharmacist. In case of oversight of the drug, 31% of patients did not take it the same day, 83% of patients were not informed on the target value of INR. Symptoms of overdose were unknown in 21% of cases. 68% did not know risks of underdosing. Treatments contraindicated were not know in 82% of cases whereas only 17% of patients did not know forbidden foods with VKA. Conclusion: Patient knowledge about their VKA treatment was insufficient to ensure the effectiveness and safety of the treatment. It would be interesting to establish a therapeutic educational programme for patients. No conflict of interest